Effect of Terrorism on the Performance of Tourism Industry. A Critical Literature Review - Muthoni, Damaris (International Journal of Modern Hospitality and Tourism, 2021)
Purpose: Global Tourism destinations provide different products which satisfy tourists with different interests, needs and wants. The general objective of the study was to examine effect of terrorism on the performance of tourism industry. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study concludes relevant governments should face the fact that terrorist attacks provoke a substitution effect on destination choice behaviors. Tourists will replace destinations considered unsafe due to terrorist threats with others considered safer. The physical distance of the tourists' home countries and their cultural and socio-economic traits influence this replacement behavior. Given the randomness of terrorist attacks, relevant governments should be prepared to alter quickly their marketing strategy, namely their market targeting strategies and promotion campaigns to prevent substitution effect and lack low returns from the tourism industry Recommendations: The study recommends that relevant governments in dealing with the root causes of terrorism should also denounce the terrorists considering their acts as criminal acts just like others. The tourism stakeholders should increase efficiency in law enforcement, prosecution of terrorist suspects, by improving intelligence gathering and the police should be effectively trained to deal with terrorism incidences. The covert nature of terrorism often precludes an easy analysis of their capabilities or intent, therefore, giving them an advantage of lying in wait and striking when least expected; thus, the government counterterrorism should be proactive